Health status and treatment outcome of tuberculosis with diabetes mellitus cases, Rajkot City, Gujarat - A longitudinal study - Harsha M Solanki; Pooja N Ranpariya; Rajesh K Chudasama (Wolters Kluwer Medknow Publications, 2023)
Background: India, with the highest number of tuberculosis (TB) cases in the world, is also facing epidemic growth in diabetes mellitus (DM). TB is curable while DM is a metabolic and incurable disease that if not controlled will affect the health status of a person. This study was conducted to assess the health status and treatment outcome of TB with DM cases. Materials and Methods: We selected a total of 64 newly registered pulmonary TB (PTB) with DM cases from five tuberculosis units (TUs) in Rajkot city from October 2019 to December 2020. At the end of treatment, 64 cases were analyzed for treatment outcome and 56 cases (5 deaths; 3 lost to follow-up) were followed up to observe progression in health status. The information was collected in pretested proforma by interview. Results: There was a significant improvement in TB symptoms (cough, weight loss, weakness, anorexia, evening rise of temperature, dyspnea, chest pain, hemoptysis), DM symptoms (frequent urination, excessive thirst and hunger, tingling and numbness), symptoms of mental health (fatigue, sleep disturbance, negative emotions, socially inactive), and adverse drug reactions (ADRs) on consecutive visits (McNemar's test, P < 0.001) and at the end of treatment (Cochran's Q test, P < 0.001). Improvement of nutritional status was also found statistically significant on consecutive visits (Wilcoxon test, P < 0.001) and at the end of treatment (Friedman's test, P < 0.001). The cure rate was 82.8% and 4.7% of cases had completed treatment. Conclusion: At the end of treatment, there was a significant improvement in health status and treatment outcome; also good cure rate was reported among cases.